When "social existence determines consciousness": the influence of political system on psychological well-being, happiness, proactive coping, and depression levels among Polish and Russian citizens - a cross-cultural study - Alexandr Erzin; Zuzanna Gazdowska; Małgorzata Piotrowska-Półrolnik (Kazimierz Wielki University, 2017)
Economic, political, and cultural crises, which many European countries are currently experiencing, increase the interest of scholars to the phenomena that positive psychology studies. The authors examine the subjective well-being, happiness, levels of depression, and proactive coping among the inhabitants of Russia and Poland - examples of similar cultures with common ethnic roots and the previous communist. The general study sample consisted of 112 people. Measures included The Ryff Psychological Well-being Scale, Oxford Happiness Questionnaire, Beck Depression Inventory, and Proactive Coping Inventory. The study found that inhabitants of Poland gained higher scores for psychological well-being and happiness. In Russia, the adults and older people have lower levels of happiness than the young. However, the Poles' depression scores were significantly higher than the Russians'. It was found that the Russian citizens increasingly use proactive coping and preventive coping. At the same time, the Poles are more likely to seek emotional support and use information resources for coping with difficulties. Correlation analysis showed that the level of depression is negatively associated with proactive coping behavior, while there is a positive link between proactive coping and psychological well-being. Research shows that some positive psychological phenomena depend on the economic, political, and social conditions in which the different countries' citizens live. Cultural and historical characteristics also determine the age-related differences. The authors believe the results presented in this article will form the basis for further research of positive mental states in Eastern Europe.